Dynamics of grain boundaries in two-dimensional colloidal crystals - Lavergne, F (2016)
The dynamics of grain boundaries in two-dimensional colloidal crystals is studied using optical microscopy and holographic optical tweezing. First, grain growth in a polycrystalline monolayer is investigated. The bond-orientational correlation function is found to satisfy scaling features predicted for systems containing random domain walls. The time-evolution of the correlation length indicates abnormal grain growth, which is shown to be due to the preferential coarsening of the large angle grain boundaries. Next, the segregation of impurities to grain boundaries is studied by embedding large spherical impurities in a polycrystalline monolayer of small colloidal spheres. The segregation behaviour is found to be in very good agreement with equilibrium grain boundary segregation, which enables the direct measurement of the free energy of adsorption. Near saturation, the formation of clusters of impurities in the boundary region is found to strongly depend on the size ratio between the impurities and the small particles, due to non-additivity effects and geometrical constraints imposed by the lattice. In order to characterise the geometry of grain boundaries, a new method to extract their geometrical features directly from microscopy images is developed. This method is used to determine the local normal direction, tangent direction and curvature of a grain boundary in a two-dimensional colloidal polycrystalline material. Further insight between the geometry and dynamics of grain boundaries is gained by analysing the shrinking kinetics of circular grain boundaries created using optical vortices. Upon increasing misorientation, these strongly curved boundaries exhibit a geometrically determined transition between pure sliding and shrinkage. In addition, the shrinking rate is found to decrease when increasing the misorientation. Dislocation reactions, which cause the reduction of the grain boundary length, are directly visualised and correlated to the kinetics of shrinkage. Finally, the dynamics of the particles during the migration of circular grain boundaries is analysed. The presence of dynamical heterogeneities is shown to be strongly determined by geometry, especially in the case of coincident site lattice boundaries where coincident particles exhibit no motion during grain boundary migration. The particle displacements involved in the motion of dislocations, which constitute the elementary mechanism of grain boundary migration, are revealed.